In vitro and in silico Studies Reveal Bacillus cereus AA-18 as a Potential Candidate for Bioremediation of Mercury-Contaminated Wastewater - Amin, Aatif; Naveed, Muhammad; Sarwar, Arslan; Rasheed, Sunbul; Saleem, Hafiz Ghulam Murtaza; Latif, Zakia; Bechthold, Andreas (Frontiers in Microbiology, 2022)
Mercury (Hg) pollution is a worldwide problem and increasing day by day due to natural and anthropogenic sources. In this study, mercury resistant (HgR) bacterial isolates were isolated from industrial wastewater of Ittehad Chemicals Ltd. Kala Shah Kaku, Lahore, Pakistan. Out of 65 bacterial isolates, five isolates were screened out based on showing resistance at 30-40 µg/mL against HgCl2. Selected Hg-resistant bacterial isolates were characterized as Bacillus subtilis AA-16 (OK562835), Bacillus cereus AA-18 (OK562834), Bacillus sp. AA-20 (OK562833) and Bacillus paramycoides AA-30 (OK562836) and Bacillus thuringiensis AA-35 (OK562837). B. cereus AA-18 showed promising results in the resistance of HgCl2 (40 µg/mL) due to presence merA gene. Scanning electron microscopy (SEM) analysis of immobilized B. cereus AA-18 showed the accumulation Hg on the cell surface. The inoculation of immobilized B. cereus AA-18 remediated 86% Hg of industrial wastewater upto 72 h at large scale (p < 0.05). In silico analysis showed structural determination of MerA protein encoded by merA gene of B. cereus AA-18 (OK562598) using Protparam, Pfam, ConSurf server, InterPro, STRING, Jpred4, PSIPRED, I-TASSER, COACH server, TrRosetta, ERRAT, VERIFY3D, Ramachandran plot and AutoDock Vina (PyRx 8.0). These bioinformatics tools predicted the structural based functional homology of MerA protein (mercuric reductase) associated with mer operon harboring bacteria involved in Hg-bioremediation system.